Use of Social Media for Collaborative Learning in Online Learning: A Literature Review - Wahyu Suci; Suyitno Muslim; Uwes Anis Chaeruman (STAI Hubbulwathan Duri, 2022)
When schools are closed to avoid face-to-face learning during this pandemic, students use social media to continue learning. Social media has become a tool for distance learning, from situations that require online learning from home. The purpose of this study was to conduct a literature study on how to accept and use social media in learning. This article summarizes insights from a recent research literature review published between 2015-2020 on how social media is accepted and used in learning. The results of the study indicate that the use of social media can be used to support learning activities. This is because social media is easy to use and popular among students, so social media can be used to support learning. From the ease of using social media in sharing learning resource information, interacting, collaborating, and discussing, of course collaborative learning outside the classroom can be realized. However, it is necessary to have good planning, management, and strategies in the use of social media to support collaborative learning, so that it can achieve the goals and needs of students' online learning.